Formy i rodzaje przemocy - Jedlecka, Wioletta (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
This article aims to present the issue of violence. Even the very definition of violenceis problematic. Violence is most often understood as an interaction betweenpeople based on the use of overwhelming force. Violence is not tantamount toaggression. What distinguishes violence is unequal power relations between theparties. When it comes to violence, power always rests with the perpetrator, while in case of aggression, it is balanced. Violence is aimed at inflicting damage to the victim, causing the victim pain and suffering, or humiliating the victim. Thereare different types of violence, e.g. sexual, psychological, physical, economic, and that caused by negligence. Furthermore, violence may be structural, symbolic, or instrumental, etc.
Keywords: violence; aggression; perpetrator; victim; suffering; humiliation